2016
DOI: 10.1038/ejcn.2016.154
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of magnesium supplementation on glucose metabolism in people with or at risk of diabetes: a systematic review and meta-analysis of double-blind randomized controlled trials

Abstract: Although higher dietary intakes of magnesium (Mg) seem to correspond to lower diabetes incidence, research concerning Mg supplementation in people with or at risk of diabetes is limited. Thus, we aimed to investigate the effect of oral Mg supplementation on glucose and insulin-sensitivity parameters in participants with diabetes or at high risk of diabetes compared with placebo. A literature search in PubMed, EMBASE, SCOPUS, Cochrane Central Register of Controlled Trials and Clinicaltrials.gov without language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 42 publications
2
66
2
Order By: Relevance
“…However, lower serum Mg may also contribute to poorer glycemic regulation and insulin sensitivity. Studies indicate that Mg supplementation improves glucose and insulin sensitivity parameters [49,50]. A meta-analysis of randomized controlled trials showed that Mg supplementation for over four months improved fasting glucose and HOMA-IR in diabetic and non-diabetic subjects [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lower serum Mg may also contribute to poorer glycemic regulation and insulin sensitivity. Studies indicate that Mg supplementation improves glucose and insulin sensitivity parameters [49,50]. A meta-analysis of randomized controlled trials showed that Mg supplementation for over four months improved fasting glucose and HOMA-IR in diabetic and non-diabetic subjects [49].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials showed that Mg supplementation for over four months improved fasting glucose and HOMA-IR in diabetic and non-diabetic subjects [49]. In another meta-analysis, Mg supplementation was shown to reduce fasting plasma glucose in diabetics and improve HOMA-IR and plasma glucose (in a 2 h oral glucose tolerance test) in persons at high risk of diabetes [50]. The mechanisms by which Mg deficiency may increase diabetes risk are poorly understood but may involve increased oxidative stress and inflammation [35,51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Mg 2+ therapy finds wide application: Mg 2+ reduces arteriolar tone and tension, increases dilatory actions of endogenous and exogenous vasodilators, and oral magnesium therapy in patients with coronary artery disease associated with significant improvement in brachial artery endothelial function and tolerance to exercise stress testing . Mg 2+ is reported to be a necessary cofactor for several enzymes in glucose metabolism, and its deficiency has an adverse effect on insulin‐mediated glucose uptake . Increased Mg 2+ level in the cerebral fluid can ease traumatic brain injury and enhance the learning abilities, working memory, and short‐ and long‐term memory in rats .…”
Section: Figurementioning
confidence: 99%
“…Proper mineral nutriture throughout life appears to be important for cognitive health, especially because magnesium can counter insulin resistance and reduce the risk of type 2 diabetes, which are known risk factors for dementia and poorer cognition (28). Studies have specifically iden-tified the association of higher magnesium intakes with reduced risk for developing MCI and low magnesium levels with increased risk (29-31).…”
Section: MCImentioning
confidence: 99%